Peran Food Presentation dan Taste dalam Membangun Kepuasan Tamu pada Restoran Padma Hotel Semarang - Sandri Insan Nurwana; Aletta Dewi Maria Th (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to analyze the role of food presentation and taste in building guest satisfaction at Semawis Restaurant, Padma Hotel Semarang. The study employed a qualitative approach with a descriptive research design to gain an in-depth understanding of guests' experiences and perceptions regarding the quality of food presentation and taste served at the restaurant. The research was conducted from January to February 2026 and involved 14 informants selected through a purposive sampling technique, consisting of one Food and Beverage Manager, one Executive Chef, one Semawis Restaurant Supervisor, three service staff members, and eight guests who had dining experience at Semawis Restaurant, Padma Hotel Semarang. Data were collected through in-depth interviews, direct observation, and documentation, and were analyzed using the interactive analysis model developed by Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. Data trustworthiness was ensured through source triangulation, method triangulation, and member checking. The findings indicate that food presentation creates guests' first impressions through aesthetic presentation, creative plating, cleanliness, and the visual appeal of dishes, thereby enhancing perceptions of food quality and the overall dining experience. Furthermore, taste reinforces guest satisfaction through the consistency of flavor, balanced seasoning, aroma, texture, and the quality of ingredients used. The study also reveals that guest satisfaction is formed through the interaction between the visual experience before consumption and the sensory experience after the meal is enjoyed, demonstrating that food presentation and taste are two complementary dimensions of food quality that jointly create a positive dining experience. These findings provide practical implications for the management of Semawis Restaurant, Padma Hotel Semarang to maintain consistent food quality while continuously developing innovative food presentation strategies to enhance guest satisfaction and strengthen the restaurant's competitiveness.